Improving Learning Outcomes in Fraction Multiplication Through Problem-Based Learning Models Assisted by Edutainment Media in Grade V - Ayu Harlinda; Somakim; Fitri Widyastuti (Jurnal Kiprah Pendidikan, 2025)
This study aims to improve students' learning outcomes in fraction multiplication material through the application of the Problem Based Learning model assisted by edutainment media in grade V of SD Negeri 55 Palembang. This study is a Classroom Action Research (CAR) which is carried out in two cycles using the Kemmis and McTaggart action model, through the stages of planning, implementation, observation, and reflection. The research subjects were 22 grade V students. Data collection techniques used learning outcome tests and observation of learning activities, which were analyzed quantitatively and qualitatively. The results showed that the average student score increased from 36.82 in the pretest to 68.73 in the post-test of cycle I, and reached 76.45 in the post-test of cycle II. The learning completeness level also increased from 0% in the pretest to 77% in the post-test of cycle II. Student learning activities increased from the category "Good" to "Very Good". This increase in learning outcomes and activeness shows that the combination of Problem Based Learning with edutainment media is able to create a more interactive and enjoyable learning atmosphere, and encourage students to better understand the material on fraction multiplication in a more systematic and contextual manner.